PENGEMBANGAN LKPD BERBASIS OSBORN PADA POKOK BAHASAN LAJU REAKSI UNTUK KELAS XI SMA/MA SEDERAJAT - angga yogi ari; susila wati; rasmi wetti (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2020)
This study aims to develop Student Worksheets Based on Osborn on the subject of valid reaction rates based on aspects of content suitability, Osborn characteristics, language, presentation, and graphics. This type of research is research and development (R and D) with reference to the Plomp development process. The subject of this study was a student worksheet based on Osborn. Data collection instrument is a validation given to three validators, and from the data analysis, the validity of the content aspect, Osborn characteristic aspects, language aspects, presentation aspects, and graphic aspects are 95.8%, 100%, 88.28%, 88.86% and 91.62% with a valid category. The student worksheet validated by the validator was tested on 30 students and got a response result with a percentage of 89.35% with very good criteria, and from two teachers got a response result with a percentage of 93.75% with very good criteria. Based on the results of data analysis, it can be concluded that the student worksheet based on OSBORN produced is valid and can be used for the subject of the reaction rate.